2020
DOI: 10.1177/1756284820905766
|View full text |Cite
|
Sign up to set email alerts
|

Teduglutide for the treatment of adults with intestinal failure associated with short bowel syndrome: pooled safety data from four clinical trials

Abstract: Background: In multiple clinical studies, teduglutide reduced parenteral support (PS) with a consistent safety profile in adults with short bowel syndrome–associated intestinal failure (SBS–IF). The objective of this study was to assess adverse events (AEs) from a pooled data set. Methods: Safety data from four prospective clinical trials of teduglutide in patients with SBS–IF were assimilated. AEs were evaluated in patient groups based on treatment received in each study and in populations stratified to creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 37 publications
4
36
0
2
Order By: Relevance
“…2 of these patients [11%] obtained complete independence from PS. Reductions in parenteral support requirements were accompanied by significant increases in mean villus height and crypt depth in this cohort as assessed by direct measurement of biopsies obtained during endoscopy [9]. HPN volume reductions were associated with improvements in quality of life scores for patients with short bowel syndrome treated with teduglutide [10] .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…2 of these patients [11%] obtained complete independence from PS. Reductions in parenteral support requirements were accompanied by significant increases in mean villus height and crypt depth in this cohort as assessed by direct measurement of biopsies obtained during endoscopy [9]. HPN volume reductions were associated with improvements in quality of life scores for patients with short bowel syndrome treated with teduglutide [10] .…”
Section: Discussionmentioning
confidence: 76%
“…Teduglutide was associated with a significantly increased risk of gastrointestinal stoma complication compared with placebo. Stoma enlargement was observed in clinical trials and in real-world clinical practice [9] . The strength of the work is that this is the first experience in our country, with very good treatment effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Pre túto liečebnú stratégiu je však potrebných ešte viac klinických údajov. Novinkou v liečbe SBS je teduglutid, rekombinantný GLP-2 (glukagon like peptide-2) analóg, ktorý zväčšuje absorpčnú plochu zvyšku tenkého čreva a umožňuje postupnú redukciu až ukončenie parenterálneho živenia (40,41).…”
Section: Kazuistikaunclassified
“…Studies in mice have suggested that teduglutide may enhance colonic carcinogenesis 5 . Until now, teduglutide treatment for up to 30 months has not been shown to increase the risk of intestinal neoplasia in human patients without any known preexisting cancer 6,7 . An international registry (NCT01990040) was set up to monitor long‐term safety, and endoscopic surveillance recommendations were suggested specifically to screen and monitor for any increased colonic neoplasia risk.…”
Section: Introductionmentioning
confidence: 99%
“…5 Until now, teduglutide treatment for up to 30 months has not been shown to increase the risk of intestinal neoplasia in human patients without any known preexisting cancer. 6,7 An international registry (NCT01990040) was set up to monitor long-term safety, and endoscopic surveillance recommendations were suggested specifically to screen and monitor for any increased colonic neoplasia risk. However, these surveillance endoscopies are limited to colonoscopies, which are recommended prior to treatment, yearly during the first 2 years, and, if without significant results, subsequently at a 5-year interval during therapy.…”
Section: Introductionmentioning
confidence: 99%